A manganese-based sodium ion battery positive electrode material for inhibiting the Jahn-Teller effect and a preparation method thereof

By depositing titanium dioxide and nitrogen-doped graphite carbon films on the surface of the positive electrode material of manganese-based sodium ion battery, the electrochemical stability problems caused by the Jahn-Teller effect are solved, and the structural stability and conductivity of the material are improved, and the electrochemical performance is significantly improved.

CN115663161BActive Publication Date: 2025-05-09LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211511005.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2025-05-09
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

In the positive electrode material of manganese oxide manganese-based sodium ion battery, the Jahn-Teller effect of Mn3+ ions leads to distortion of the local lattice structure, reducing electrochemical stability.

Method used

The titanium dioxide film was deposited as the cladding layer by using high-power magnetron sputtering technology, and then the nitrogen-doped graphite carbon film was deposited using the intermediate frequency magnetron sputtering technology to form a stable coating structure and suppress the Jahn-Teller effect.

Benefits of technology

Through the coating of titanium dioxide and nitrogen-doped graphite carbon films, the structural stability and conductivity of the material are improved, and the electrochemical performance is enhanced, including good rate performance and excellent cycling stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 221129162943
    Figure 221129162943
Patent Text Reader

Abstract

The present invention discloses a manganese-based sodium ion battery positive electrode material that suppresses the Jahn-Teller effect, which is to first deposit a titanium dioxide film on the surface of the manganese-based sodium ion battery positive electrode material using a high-power magnetron sputtering technique, and then deposit a nitrogen-doped graphite carbon film using a medium-frequency magnetron sputtering technique. The titanium dioxide coating layer provides a framework structure, effectively isolates the material from the electrolyte, avoids the material from dissolving in the electrolyte to cause irreversible losses, effectively suppresses the Jahn-Teller effect, and improves the stability of the material structure; the nitrogen-doped graphite carbon coating layer can effectively improve the electrical conductivity of the positive electrode material, thereby comprehensively improving the electrochemical properties of the material. The preparation process of the present invention does not involve liquid phase reaction conditions, can effectively avoid the introduction of impurities, the prepared film has good bonding strength, the experimental process is highly controllable, efficient, and less polluting, and has broad market application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a manganese-based sodium ion battery positive electrode material, in particular to a manganese-based sodium ion battery positive electrode material capable of suppressing the Jahn-Teller effect and a preparation method thereof, and belongs to the technical fields of composite materials and battery materials. Background Art

[0002] The widespread use of fossil energy has made environmental pollution and energy crisis two major world problems. The development of new energy devices based on electrochemistry is of great significance to reducing environmental pollution and solving the energy crisis. Because lithium reserves in the earth's crust are relatively scarce and sodium reserves are abundant, sodium-ion batteries (SIBs) have aroused the interest of more and more industrial sectors / scientific researchers as energy storage devices to replace lithium-ion batteries (LIBs). Manganese resources are abundant in the earth's crust and the cost is low. Manganese-based materials have made great progress as positive electrode materials for sodium-ion batteries. Among them, sodium manganese oxide positive electrode materials NaxMnO2 with different sodium contents (x) show interesting battery performance and have received widespread attention. However, for most layered (x>0.5) and tunnel-type (x<0.5) manganese oxides, during the charge and discharge process, after Mn4+ is reduced to Mn3+, the Jahn-Teller effect caused by Mn3+ ions greatly distorts the local lattice structure and reduces the electrochemical stability.

[0003] To solve the above problems, Chinese patent CN115224265 A discloses a modified sodium ion battery positive electrode material and a preparation method and application thereof. The preparation method uses sodium pyrophosphate metal salt as the sodium ion battery positive electrode material as the core, and arranges a carbon coating layer and an AlPO4 coating layer on the surface of the core to form an egg yolk shell structure; Chinese patent CN115295790 A discloses a modified sodium ion battery positive electrode material and a preparation method and application thereof, comprising the following steps: (1) adding a titanium source compound, an aluminum source compound, and a β-diketone stabilizer to a solvent, and dissolving them fully to obtain a liquid A; (2) dissolving a sodium-containing compound in deionized water to obtain a readily soluble alkaline solution, and adding the liquid A to the readily soluble alkaline solution to obtain a liquid B; (3) adding the sodium ion battery positive electrode material to the liquid B, stirring them fully, and drying them to obtain a mixed powder; (4) subjecting the obtained mixed powder to heat treatment, crushing and sieving, to obtain a coated sodium ion battery positive electrode material. However, in the above schemes, liquid phase reaction conditions exist during the formation of the coating layer, which is easy to introduce impurities; the coating layer has weak bonding strength and uncontrollable thickness, which greatly limits the improvement of the material structure stability; furthermore, the preparation process of the above scheme is complicated and difficult to achieve industrial production. Summary of the invention

[0004] In view of the above technical problems, the present invention provides a manganese-based sodium ion battery positive electrode material that suppresses the Jahn-Teller effect and a preparation method thereof.

[0005] The manganese-based sodium ion battery positive electrode material for inhibiting the Jahn-Teller effect of the present invention is to first deposit a titanium dioxide film on the surface of the manganese-based sodium ion battery positive electrode material using a high-power magnetron sputtering technique, and then deposit a nitrogen-doped graphite-like carbon film using a medium-frequency magnetron sputtering technique. The specific preparation process is as follows:

[0006] (1) After drying the NaxMnO2 electrode powder, place it on the rotating frame of the vacuum coating chamber of the magnetron sputtering device, adjust the target spacing and evacuate to 10-4 Pa. NaxMnO2 includes tunnel-type oxides when x < 0.5 and layered P2 structure oxides when x > 0.5. The NaxMnO2 electrode powder is dried in an oven at 110 ° C under vacuum conditions for 120 min;

[0007] (2) Argon gas was introduced, and the working pressure of the chamber was adjusted to 1.1 Pa. High-power magnetron sputtering technology was used to sputter the titanium dioxide target to deposit a titanium dioxide film. The duty cycle of the high-power power supply was 0.1, the current of the titanium dioxide target was 0.8~1A, and the output power was 400~500W. The thickness of the titanium dioxide film was 8nm;

[0008] (3) Nitrogen was introduced, and the argon:nitrogen flow ratio was adjusted to 5:1~2:1, so that the chamber working pressure was maintained at 1.1 Pa, and the nitrogen-doped graphite carbon film was deposited by medium frequency magnetron sputtering technology. Among them, the duty cycle of the medium frequency power supply was 0.6, the current of the graphite target was 1A, and the output power was 600W. The thickness of the obtained nitrogen-doped graphite carbon film was 9nm.

[0009] Schematic diagram of the structure of the manganese-based sodium ion battery positive electrode material that suppresses the Jahn-Teller effect prepared by the present invention. The titanium dioxide coating layer provides a framework structure to improve the structural stability of the material; the nitrogen-doped graphite-like carbon coating layer can effectively improve the conductivity of the positive electrode material. At the same time, the titanium dioxide and carbon coating layers can prevent the electrolyte from directly contacting the active material, and can stabilize the electron transmission speed and ion diffusion rate at the solid / liquid interface, thereby comprehensively improving the electrochemical performance of the material. The prepared manganese-based sodium ion battery positive electrode material was assembled into a sodium ion half-cell, which exhibited good rate performance and excellent cycle stability in the electrolyte (1.0MNaClO4 in PC:FEC=95:5 Vol%).

[0010] The present invention has the following beneficial effects compared with the prior art:

[0011] 1. The present invention deposits a titanium dioxide film coating layer on the surface of the positive electrode material of the manganese-based sodium ion battery, which can effectively isolate the material from the electrolyte, prevent the material from dissolving in the electrolyte and causing irreversible loss, effectively inhibit the Jahn-Teller effect, and ensure the thermal stability of the material; by further depositing a nitrogen-doped graphite-like carbon film, the conductivity of the positive electrode material is effectively improved. At the same time, nitrogen doping can increase active sites and facilitate the transmission of sodium ions, thereby comprehensively improving the electrochemical performance of the material;

[0012] 2. The preparation process of the present invention does not involve liquid phase reaction conditions, which can effectively avoid the introduction of impurities. The prepared film has good bonding strength, the experimental process is highly controllable, efficient, and has little pollution, and has broad market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a schematic diagram of the structure of the manganese-based sodium ion battery positive electrode material for suppressing the Jahn-Teller effect prepared by the present invention. DETAILED DESCRIPTION

[0014] The preparation and performance of the manganese-based sodium ion battery positive electrode material for suppressing the Jahn-Teller effect of the present invention are described in detail below in conjunction with specific examples.

[0015] Example 1

[0016] (1) Experimental conditions for thin film deposition: NaxMnO2 (x≤1) electrode powder was baked in an oven at 110°C under vacuum for 120 min and then placed on the rotating rack in the vacuum coating chamber of the magnetron sputtering device. The target spacing was adjusted and the vacuum was evacuated to 10-4 Pa. The rotating rack and sputtering target were turned on.

[0017] (2) Preparation of titanium dioxide film: Argon gas was introduced, and the working pressure of the chamber was adjusted to 1.1 Pa. The titanium dioxide target was sputtered using high-power magnetron sputtering technology to deposit titanium dioxide film: the duty cycle of the high-power power supply was 0.1, the titanium dioxide target current was 1A, the output power was 500W, and the thickness of the titanium dioxide film was 8nm;

[0018] (3) Preparation of nitrogen-doped graphite carbon film: nitrogen was introduced, the gas flow ratio of argon and nitrogen was adjusted to 5:1, the chamber pressure was maintained at 1.1 Pa, and the graphite target was sputtered using medium frequency magnetron sputtering technology to deposit nitrogen-doped graphite carbon film: the medium frequency power supply duty cycle was 0.1, the graphite target current was 1A, the output power was 600W, and the nitrogen-doped graphite carbon film thickness was 9 nm;

[0019] (4) It was assembled into a sodium ion half-cell. In the electrolyte (1.0M NaClO4 in PC:FEC=95:5 Vol%), at current densities of 0.1C, 0.5C, 1C and 2C, its first-cycle test discharge specific capacity can reach 111.5mAh / g, 108.5mAh / g, 105.1mAh / g and above 101.3mAh / g, respectively, showing good rate performance; at a current density of 0.1C, after 100 cycles, its specific capacity can reach above 99.3 mAh / g, showing excellent cycle stability.

[0020] Example 2

[0021] (1) Experimental conditions for thin film deposition: NaxMnO2 (x≤1) electrode powder was baked in an oven at 110°C under vacuum for 120 min and then placed on the rotating rack in the vacuum coating chamber of the magnetron sputtering device. The target spacing was adjusted and the vacuum was evacuated to 10-4 Pa. The rotating rack and sputtering target were turned on.

[0022] (2) Preparation of titanium dioxide thin film: Argon gas was introduced, and the working pressure of the chamber was adjusted to 1.1 Pa. Titanium dioxide was sputtered using high-power magnetron sputtering technology to deposit titanium dioxide thin film: the duty cycle of the high-power power supply was 0.1, the titanium dioxide target current was 0.8 A, the output power was 400 W, and the thickness of the titanium dioxide film was 8 nm;

[0023] (3) Preparation of nitrogen-doped graphite carbon film: nitrogen was introduced, the gas flow ratio of argon and nitrogen was adjusted to 2:1, the chamber pressure was maintained at 1.1 Pa, and the graphite target was sputtered using medium frequency magnetron sputtering technology: the duty cycle of the medium frequency power supply was 0.1, the current of the graphite target was 1A, the output power was 600W, and the thickness of the nitrogen-doped graphite carbon film was 9 nm;

[0024] (4) It was assembled into a sodium ion half-cell. In the electrolyte (1.0M NaClO4 in PC:FEC=95:5 Vol%), at current densities of 0.1C, 0.5C, 1C and 2C, its first cycle test discharge capacity can reach 109.9mAh / g, 106.5mAh / g, 102.1mAh / g and above 99.5mAh / g, respectively, showing good rate performance. At a current density of 0.1C, after 100 cycles, its specific capacity can reach above 101.2mAh / g, showing excellent cycle stability.

[0025] Example 3

[0026] (1) Experimental conditions for thin film deposition: NaxMnO2 (x≤1) electrode powder was baked in an oven at 110°C under vacuum for 120 min and then placed on the rotating rack in the vacuum coating chamber of the magnetron sputtering device. The target spacing was adjusted and the vacuum was evacuated to 10-4 Pa. The rotating rack and sputtering target were turned on.

[0027] (2) Preparation of titanium dioxide film: Argon gas was introduced and the working pressure of the chamber was adjusted to 1.1 Pa. High-power magnetron sputtering technology was used to sputter the titanium dioxide target to deposit the titanium dioxide film: the duty cycle of the high-power power supply was 0.1, the titanium dioxide target current was 0.9 A, the output power was 450 W, and the thickness of the titanium dioxide film was 8 nm;

[0028] (3) Preparation of nitrogen-doped graphite carbon film: nitrogen was introduced, the gas flow ratio of argon and nitrogen was adjusted to 3:1, the chamber pressure was maintained at 1.1 Pa, and the graphite target was sputtered using medium frequency magnetron sputtering technology to deposit nitrogen-doped graphite carbon film: the medium frequency power supply duty cycle was 0.1, the graphite target current was 1A, the output power was 600W, and the thickness of the nitrogen-doped graphite carbon film was 9 nm;

[0029] (4) It was assembled into a sodium ion half-cell. In the electrolyte (1.0M NaClO4 in PC:FEC=95:5 Vol%), at current densities of 0.1C, 0.5C, 1C and 2C, its first cycle test discharge capacity can reach 113.1mAh / g, 107.5mAh / g, 103.1mAh / g and 101.5mAh / g or more, respectively, showing good rate performance. At a current density of 0.1C, after 100 cycles, its specific capacity can reach more than 105.2mAh / g, showing excellent cycle stability.

[0030] Comparative Example: The NaxMnO2 (x≤1) positive electrode material without surface coating was prepared into a sodium ion half-cell. In the electrolyte (1.0M NaClO4 in PC:FEC=95:5 Vol%), at current densities of 0.1C, 0.5C, 1C and 2C, its first cycle test discharge capacity can reach 70.1mAh / g, 62.3mAh / g, 57.3mAh / g and 50.5mAh / g respectively. At a current density of 0.1C, after 100 cycles, its specific capacity is 43.1mAh / g.

Claims

1. A method for preparing a manganese-based sodium ion battery positive electrode material that inhibits the Jahn-Teller effect, which is to first deposit a titanium dioxide film on the surface of the manganese-based sodium ion battery positive electrode material using a high-power magnetron sputtering technique, and then deposit a nitrogen-doped graphite-like carbon film using a medium-frequency magnetron sputtering technique; the method specifically includes the following process steps: (1) After drying the NaxMnO2 electrode powder, place it on the rotating frame of the vacuum coating chamber of the magnetron sputtering device, adjust the target spacing and evacuate to 10 -4 Pa; in the NaxMnO2, x≤1; (2) introducing argon gas, adjusting the chamber working pressure to 1.1 Pa, and using high-power magnetron sputtering technology to sputter the titanium dioxide target to deposit a titanium dioxide film; (3) Nitrogen was introduced and the flow ratio of argon to nitrogen was adjusted to 5:1-2:

1. The working pressure of the chamber was maintained at 1.1 Pa. The graphite target was sputtered using medium-frequency magnetron sputtering technology to deposit nitrogen-doped graphite-like carbon film.

2. The method for preparing a manganese-based sodium ion battery positive electrode material for suppressing the Jahn-Teller effect as claimed in claim 1, characterized in that: In step (1), the drying is carried out in an oven at 110°C under vacuum conditions for 120 min.

3. The method for preparing a manganese-based sodium ion battery positive electrode material for suppressing the Jahn-Teller effect as claimed in claim 1, characterized in that: In step (2), the duty cycle of the high-power power supply is 0.1, the current of the titanium dioxide target is 0.8-1A, and the output power is 400-500W.

4. The method for preparing a manganese-based sodium ion battery positive electrode material for suppressing the Jahn-Teller effect as claimed in claim 1, characterized in that: In step (2), the thickness of the titanium dioxide film is 8 nm.

5. The method for preparing a manganese-based sodium ion battery positive electrode material for suppressing the Jahn-Teller effect as claimed in claim 1, characterized in that: In step (3), the duty cycle of the medium frequency power supply is 0.6, the current of the graphite target is 1A, and the output power is 600W.

6. The method for preparing a manganese-based sodium ion battery positive electrode material for suppressing the Jahn-Teller effect as claimed in claim 1, characterized in that: The thickness of the nitrogen-doped graphite-like carbon film obtained in step (3) is 9 nm.

Citation Information

Patent Citations

  • Modified sodium ion battery positive electrode material and preparation method and application thereof

    CN115224265A

  • Coating method of sodium ion battery positive electrode material

    CN115295790A

  • Preparation method of sodium ion battery positive electrode material with coating structure

    CN112456567A

  • KR20200042293A